Structure of a polychaete community in a mangrove in the northern coast of Brazil (2018)
Polychaetes play an important role in the structure and functioning of benthic communities in mangroves; however, knowledge about these organisms in the Maranhão Amazon coast is scarcity. This study analyzed the ecological aspects of polychaete community in the Quebra Pote mangrove in Maranhão State. Four sampling campaigns were carried out during both rainy and dry periods between November 2013 and July 2014, using 100 meters long transects set perpendicular to the waterline at three zones 50 m between them. A total of 521 organisms were identified belonging to ten families and 15 species; Nephtys simoni, Notomastus sp., and Paraonis sp. represented 58.92 % of all samples. Mobile deposit-feeders polychaetes were dominant and abundant. The Quebra Pote mangrove showed high values of diversity and evenness. The spatial distribution indicated that several species such as Capitella sp., Heteromastus sp., N. simoni, Notomastus sp., Paradoneis sp., Paraonis sp., Scoloplos texana, Sigambra grubei, and Syllis gracilis magellanica were present in all mangrove zones. The diversity and abundance of polychaetes were greater in lower mesolittoral (Zone 1), with a dominance of Avicennia schaueriana. The abundance of polychaetes decreased along transects from the lower mesolittoral to upper mesolittoral areas, suggesting that the presence of domestic sewage effects supersedes the vegetation effect.